THE ROLE OF RELIGIOUS COURTS IN PROTECTING WOMEN'S RIGHTS IN DISTRIBUTION OF JOINT PROPERTY - Rasyidin, Rasyidin; Eriani, Dian; Soraya, Ade (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aims to review the discussion on how the role of the Religious Courts towards the protection of women's rights in the distribution of joint assets in the decision Number 4698/Pdt.G/2019/PA.Tgrs and also how the considerations of the Religious Court Judges based on the Decision Number 4698/Pdt.G/2019 /PA.Tgrs. The research method used is normative juridical with a conceptual approach and a statutory approach. Data analysis uses a qualitative approach. The Religious Courts in protecting women's rights in cases of the distribution of joint property have a role and function to examine, adjudicate and decide on a case applying human rights values with respect for human dignity, non-discrimination, equality before the law, justice, benefit, legal certainty, and ex officio judges provide protection for women, by giving 70% of joint property to women and 30% to men by ignoring the Marriage Law and the Compilation of Islamic Law. Consideration of judges who ignore women's rights and have a patriarchal mindset towards child support. It is the duty of a man to provide for his children, an obligation that is neglected causes a man to be able to collect wealth while a woman to provide a living for children is the cause of not being able to collect wealth. Judges should consider this to create legal justice.